Electrical Study of Al/n-ZnS Schottky Junction on Polymer Substrate - Gupta, Sandhya; Saxena, N.S.; Sharma, Kananbala (Journal of Research Updates in Polymer Science, 2013)
A study has been made on the behaviour of Al/n-ZnS thin film junction on Polyethylene terephthalate (PET) grown using thermal evaporation method. Current-Voltage (I-V) characteristics of this junction show that the Aluminium (Al) makes Schottky contact with n-ZnS (Zinc Sulfide). Intrinsic and contact properties such as saturation current, barrier height, ideality factor and series resistance were calculated from the I-V characteristics. The conduction seems to be predominantly due to thermoionic emission-diffusion mechanism. An effort has also been made to carry out the optical study of ZnS thin film using spectrophotometer. Band gap of n-ZnS thin film is determined through absorption spectra using the Tauc’s extrapolation. A band diagram of Al/n-ZnS has been proposed using the so obtained data.